The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/cells12131724
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Preservation of Ovine Periosteum Using a Perfusion Bioreactor System

Abstract: Periosteum is a highly vascularized membrane lining the surface of bones. It plays essential roles in bone repair following injury and reconstruction following invasive surgeries. To broaden the use of periosteum, including for augmenting in vitro bone engineering and/or in vivo bone repair, we have developed an ex vivo perfusion bioreactor system to maintain the cellular viability and metabolism of surgically resected periosteal flaps. Each specimen was placed in a 3D printed bioreactor connected to a perista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, the use of a periosteum for scaffold fabrication requires a feasible ex vivo approach in which the tissue viability of the harvested periosteum is preserved. Xin et al used a perfusion bioreactor system as demonstrated in Figure 3 in which an ovine periosteal flap was placed in a 3-D printed bioreactor and perfused with a culture medium via its artery [ 15 ]. Both live and dead assays, PrestoBlue assays, and a histology analysis suggested that a significant proportion of cells were still viable after being perfused for up to 4 weeks.…”
Section: In Vivo and Ex Vivo Periosteal Bioreactor Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the use of a periosteum for scaffold fabrication requires a feasible ex vivo approach in which the tissue viability of the harvested periosteum is preserved. Xin et al used a perfusion bioreactor system as demonstrated in Figure 3 in which an ovine periosteal flap was placed in a 3-D printed bioreactor and perfused with a culture medium via its artery [ 15 ]. Both live and dead assays, PrestoBlue assays, and a histology analysis suggested that a significant proportion of cells were still viable after being perfused for up to 4 weeks.…”
Section: In Vivo and Ex Vivo Periosteal Bioreactor Systemsmentioning
confidence: 99%
“…As a proof-of-concept study, the proposed ex vivo perfusion system was shown to be a feasible solution for preserving a harvested periosteum for a prolonged period for upcoming scaffold vascularization. However, several key system parameters still need to be optimized, such as the flow rate, pressure, and culture medium formulation [ 15 ]. These factors have been proven important in previous similar studies in which the researchers attempted to perfuse scaffold constructs seeded with osteogenic cells to study bone biology, proliferation, and gene expression [ 74 , 75 , 76 ].…”
Section: In Vivo and Ex Vivo Periosteal Bioreactor Systemsmentioning
confidence: 99%
See 3 more Smart Citations